Analisis Pengaruh Pemberdayaan dan Kinerja Usaha terhadap Kesejahteraan Pelaku Usaha Kerajinan di Kabupaten Rote Ndao - Danira Irin Wijayanti (OPTIMAL Jurnal Ekonomi dan Manajemen, 2024)
Rote Ndao Regency has abundant resource potential in cultural preservation, where this potential is used by the local community for business resources by producing handicrafts. The development of handicraft businesses run by the community can certainly contribute to the economy and welfare of the people in the region. However, based on data from the Central Bureau of Statistics, what is currently happening is that the welfare level of the people of Rote Ndao is still relatively low due to the lack of development of handicraft products produced by artisans. For this reason, this study aims to: 1) Know and analyze the effect of empowerment on the welfare of handicraft entrepreneurs in Rote Ndao Regency; 2) Knowing and analyzing the effect of business performance on the welfare of handicraft business actors in Rote Ndao Regency. The sample in this study were 70 respondents who were handicraft entrepreneurs in Rote Ndao Regency. Data analysis technique using multiple linear regression. The results of the study show that both business empowerment and business performance variables have a positive and significant effect on the welfare of craft business actors in Rote Ndao Regency.